Tingkat Kecerdasan Emosi Peserta Didik Kelas XI di SMA Negeri 15 Palembang - Lestari, Diana Putri; Sofah, Rahmi; Putri, Rani Mega (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2019)
This research aims to determined the level of emotional quotient of eleventh grade students in SMA Negeri 15 Palembang. This research uses a quantitative descriptive approach with survey method. Data collection technique used is a questionnaire consisting of five aspects, namely: self-awareness, self-regulation, motivation, empathy, and fostering relationships. The population in this research were eleventh grade students of SMA Negeri 15 Palembang which amounted to 244 people. The sample in this research amounted to 56 people selected by using a purposive sampling technique. The results of data analysis shows that 32 percent students in eleventh grade had emotional quotient with a high category that was 65% while the category and 3% low category.